DAMPAK STOCK SPLIT TERHADAP HARGA SAHAM DAN AKTIVITAS VOLUME PERDAGANGAN SAHAM DI BURSA EFEK INDONESIA - Yuniartini, Ni Kadek Wiwik; Sedana, Ida Bagus Panji (E-Jurnal Manajemen, 2020)
Stock Split is an activity carried out by a company by breaking down the nominal value of shares into smaller ones. Stock split policy has an impact on stock prices and stock trading volume activity. The purpose of this study was to determine the significance of the impact of stock split on stock prices and stock trading volume activity. This research was conducted on companies listed on the Indonesia Stock Exchange with  stock split on 2016-2018 with 47 samples. Data collected through www.idx.co.id. Wilcoxon signed rank test was used. The results of this study indicate that stock split has an impact on stock prices seen through a significant difference in stock prices before and after a stock split. Stock split does not have an impact on stock trading volume activity measured through trading volume activity which shows no significant difference in trading volume activity before and after stock split. Keywords: Stock Split, Stock Price, Trading Volume Activity.